Educator Recruitment Management in Improving Student Quality at Dwiwarna Parung High School - Amrulloh, Nadhir M. Abdul Ghofur (JERIT: Journal of Educational Research and Innovation Technology, 2024)
Recruitment management is very important in schools because students need teachers who are professional in the teaching process and can motivate children so as to increase student creativity, increase student innovation and make students successful. The aim of this research is to determine the management of teacher recruitment for the quality of education at Dwiwarna High School, to find out the obstacles in the management of human resource recruitment in improving the quality of education at Dwiwarna High School, to find out the anticipations made in resolving obstacles to the management of teaching staff recruitment in improving the quality of education. at Dwiwarna High School. Qualitative research methods, data collection techniques and procedures: observation, interviews, documentation. The results of research on a series of teacher recruitment processes at Dwiwarna High School are analysis of teaching staff needs, recruitment strategies, recruitment media, receiving application files, file selection, interviews, micro teaching, announcements and placements. Obstacles in the recruitment of teaching staff will of course be experienced in line with competitors of other institutions that have superior school quality and must be anticipated by improving the quality of education, infrastructure and values stated in school accreditation so that prospective teaching staff see and are also interested. to apply to Dwiwarna Parung High School.